The Mexican Assimilation: Colombia in the 1930s - The case of Ignacio Gómez Jaramillo (2013)
During the 1930s in Colombia, artists such as Ignacio Gómez Jaramillo, took Mexican muralism as an important part of their careers thus engaging with public art for the irst time in the country. In 1936, Gómez Jaramillo travelled to Mexico for two years in order to study muralism, to learn the fresco technique and to transmit the Mexican experience of the open-air-schools. Gómez Jaramillo returned to Colombia in 1938 and in 1939 painted the murals of the National Capitol. Although Gómez Jaramillo’s work after 1939 is well known, his time in Mexico has been barely studied and very few scholars have analyzed the artist’s work in light of his Mexican experience. While in Mexico, Gómez Jaramillo joined the LEAR (La Liga de Escritores y Artistas Revolucionarios) with whom he crated the murals of the Centro Escolar Revolución. These murals depict politically engaged images that, apparently, little had to do with his more historical work back in Colombia. This text proposes a careful reading of the artist’s work at the CER and a rereading of the National Capitol murals in light of a more politicized vision.